Anthropogenic microparticles in sediments related to landuse in Pantanal wetlands, Brazil - Camargo, Alan Lacerda Gomes (2021)
The amount research on microplastics (<5mm) have increased in recent years. These particles involve potential impacts on ecosystem and biota due to their ease of ingestion by organisms, trophic transfer, or their high capacity to accumulate in the environment. However, there are still few studies on this type of pollution in wetlands which provide a great share of environmental services. We investigated the density (n/m²), size and the variables related to the distribution of microplastics in fluvial sediments of the Cuiabá River, one of the main tributaries of the Pantanal, the world largest flooded savanna. Eleven of the 15 sampling points were in the Pantanal floodplain and the rest on the plateau region surrounding it. On average, 576.8±577.8 microplastics particles per square meter of sediments were found, composed of fragments (309.0±319.6 n/m2) and fibers (267.8±339.9 n/m2). The maximum density was 1938.8 n/m² found in the urban stretch of the cities of Cuiabá and Várzea Grande in the metropolitan region. Blue synthetic fibers, whose complex composition, including Pb, Li and Nb, suggests that they may come from electronic waste, were the most abundant (240.7±310.4 n/m2), followed by Polypropylene (159.2±133.4 n/m2) and Polyvinyl Chloride (104.6±217.2 n/m2). The average size in sampling sites ranged from 0.18 mm to 1.74 mm. Microplastics densities was statistically associated to urban areas. Their average size was also found to decrease with distance from the study area’s main urban agglomeration. These results suggest that urban areas along the Cuiabá River are a major source of microplastic pollution in the study area. More studies must be carried out to investigate the potential impacts of these particles on terrestrial and aquatic biota.